Solve for t -1/2*(t+9)+5 3/4*t=3/8t

Math
-12⋅(t+9)+534⋅t=38t
Simplify -12⋅(t+9)+534⋅t.
Tap for more steps…
Convert 534 to an improper fraction.
Tap for more steps…
A mixed number is an addition of its whole and fractional parts.
-12⋅(t+9)+(5+34)⋅t=38t
Add 5 and 34.
Tap for more steps…
To write 5 as a fraction with a common denominator, multiply by 44.
-12⋅(t+9)+(5⋅44+34)⋅t=38t
Combine 5 and 44.
-12⋅(t+9)+(5⋅44+34)⋅t=38t
Combine the numerators over the common denominator.
-12⋅(t+9)+5⋅4+34⋅t=38t
Simplify the numerator.
Tap for more steps…
Multiply 5 by 4.
-12⋅(t+9)+20+34⋅t=38t
Add 20 and 3.
-12⋅(t+9)+234⋅t=38t
-12⋅(t+9)+234⋅t=38t
-12⋅(t+9)+234⋅t=38t
-12⋅(t+9)+234⋅t=38t
Simplify each term.
Tap for more steps…
Apply the distributive property.
-12t-12⋅9+234⋅t=38t
Combine t and 12.
-t2-12⋅9+234⋅t=38t
Multiply -12⋅9.
Tap for more steps…
Multiply 9 by -1.
-t2-9(12)+234⋅t=38t
Combine -9 and 12.
-t2+-92+234⋅t=38t
-t2+-92+234⋅t=38t
Move the negative in front of the fraction.
-t2-92+234⋅t=38t
Combine 234 and t.
-t2-92+23t4=38t
-t2-92+23t4=38t
To write -t2 as a fraction with a common denominator, multiply by 22.
-t2⋅22+23t4-92=38t
Write each expression with a common denominator of 4, by multiplying each by an appropriate factor of 1.
Tap for more steps…
Multiply t2 and 22.
-t⋅22⋅2+23t4-92=38t
Multiply 2 by 2.
-t⋅24+23t4-92=38t
-t⋅24+23t4-92=38t
Combine the numerators over the common denominator.
-t⋅2+23t4-92=38t
Simplify each term.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Factor t out of -t⋅2+23t.
Tap for more steps…
Factor t out of -t⋅2.
t(-1⋅2)+23t4-92=38t
Factor t out of 23t.
t(-1⋅2)+t⋅234-92=38t
Factor t out of t(-1⋅2)+t⋅23.
t(-1⋅2+23)4-92=38t
t(-1⋅2+23)4-92=38t
Multiply -1 by 2.
t(-2+23)4-92=38t
Add -2 and 23.
t⋅214-92=38t
t⋅214-92=38t
Move 21 to the left of t.
21t4-92=38t
21t4-92=38t
21t4-92=38t
Combine 38 and t.
21t4-92=3t8
Move 3t8 to the left side of the equation by subtracting it from both sides.
21t4-92-3t8=0
Simplify 21t4-92-3t8.
Tap for more steps…
To write 21t4 as a fraction with a common denominator, multiply by 22.
21t4⋅22-3t8-92=0
Write each expression with a common denominator of 8, by multiplying each by an appropriate factor of 1.
Tap for more steps…
Multiply 21t4 and 22.
21t⋅24⋅2-3t8-92=0
Multiply 4 by 2.
21t⋅28-3t8-92=0
21t⋅28-3t8-92=0
Combine the numerators over the common denominator.
21t⋅2-3t8-92=0
Simplify each term.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Factor 3t out of 21t⋅2-3t.
Tap for more steps…
Factor 3t out of 21t⋅2.
3t(7⋅2)-3t8-92=0
Factor 3t out of -3t.
3t(7⋅2)+3t(-1)8-92=0
Factor 3t out of 3t(7⋅2)+3t(-1).
3t(7⋅2-1)8-92=0
3t(7⋅2-1)8-92=0
Multiply 7 by 2.
3t(14-1)8-92=0
Subtract 1 from 14.
3t⋅138-92=0
3t⋅138-92=0
Multiply 13 by 3.
39t8-92=0
39t8-92=0
39t8-92=0
Find the LCD of the terms in the equation.
Tap for more steps…
To find the LCD of a set of numbers (39t8,-92), find the LCM of the denominators.
LCM(8,2)
Calculate the LCM of first two denominators in the list, 8 and 2.
Tap for more steps…
Find the values of the numerical part of each term. Select the largest one, which in this case is 8. Multiply them together to get the current total. In this case, the current total is 16.
Current Total = 16
Check each value in the numerical part of each term against the current total. Since the current total is evenly divisible, return it. That is the least common denominator of the numerical part of the fraction.
8
8
8
Multiply each term by 8 and simplify.
Tap for more steps…
Multiply each term in 39t8-92=0 by 8.
39t8⋅8-92⋅8=0⋅8
Simplify each term.
Tap for more steps…
Cancel the common factor of 8.
Tap for more steps…
Cancel the common factor.
39t8⋅8-92⋅8=0⋅8
Rewrite the expression.
39t-92⋅8=0⋅8
39t-92⋅8=0⋅8
Cancel the common factor of 2.
Tap for more steps…
Move the leading negative in -92 into the numerator.
39t+-92⋅8=0⋅8
Factor 2 out of 8.
39t+-92⋅(2(4))=0⋅8
Cancel the common factor.
39t+-92⋅(2⋅4)=0⋅8
Rewrite the expression.
39t-9⋅4=0⋅8
39t-9⋅4=0⋅8
Multiply -9 by 4.
39t-36=0⋅8
39t-36=0⋅8
Multiply 0 by 8.
39t-36=0
39t-36=0
Add 36 to both sides of the equation.
39t=36
Divide each term by 39 and simplify.
Tap for more steps…
Divide each term in 39t=36 by 39.
39t39=3639
Cancel the common factor of 39.
Tap for more steps…
Cancel the common factor.
39t39=3639
Divide t by 1.
t=3639
t=3639
Cancel the common factor of 36 and 39.
Tap for more steps…
Factor 3 out of 36.
t=3(12)39
Cancel the common factors.
Tap for more steps…
Factor 3 out of 39.
t=3⋅123⋅13
Cancel the common factor.
t=3⋅123⋅13
Rewrite the expression.
t=1213
t=1213
t=1213
t=1213
The result can be shown in multiple forms.
Exact Form:
t=1213
Decimal Form:
t=0.923076‾
Solve for t -1/2*(t+9)+5 3/4*t=3/8t

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top